Effect of Tie-2 conditional deletion of BDNF on atherosclerosis in the ApoE null mutant mouse - Norata, Giuseppe; Venu, V.; Callegari, E.; Paloschi, V.; Catapano, A. (Elsevier BV, 2012)
The reduced expression (haplodeficiency) of the main brain derived neurotrophic factor receptor, namely TrkB is associated with reduced atherosclerosis, smooth muscle cells accumulation and collagen content in the lesion. These data support the concept that brain derived neurotrophic factor of vascular origin may contribute to atherosclerosis. However, to date, no experimental approach was possible to investigate this issue due to the lethality of brain derived neurotrophic factor null mice. To overcome these limitations, we generated a mouse model with a conditional deletion of brain derived neurotrophic factor in endothelial cells (Tie-2 Cre recombinase) on an atherosclerotic prone background (apolipoprotein E knock out) and investigated the effect of conditional brain derived neurotrophic factor deficiency on atherosclerosis. Despite brain derived neurotrophic factor reduction in the vascular wall, mice with conditional deletion of brain derived neurotrophic factor did not develop larger atherosclerotic lesion compared to controls. Smooth muscle cell content as well as the distribution of total and fibrillar collagen was similar in the atherosclerotic lesions from mice with brain derived neurotrophic factor conditional deficiency compared to controls. Finally an extended gene expression analysis failed to identify pro-atherogenic gene expression patterns among the animal with brain derived neurotrophic factor deficiency. In spite of the reduced brain derived neurotrophic factor expression, similar atherosclerosis development was observed in the brain derived neurotrophic factor conditional deficient mouse compared to controls. These pieces of evidence indicate that endothelial derived-brain derived neurotrophic factor is not a pro-atherogenic factor and would rather suggest to investigate the role of other TrkB activators on atherosclerosis. © 2012 Elsevier B.V.